Assessment of Equivalent Thickness Design Principles for Geosynthetic Reinforced Pavements by Way of Accelerated Testing. Issue 40 (December 2018) - Robinson, W. Jeremy; Tingle, Jeb. S.; Norwood, Gregory J.; Howard, Isaac L.
The Engineer Research and Development Center (ERDC) of the U.S. Army Corps of Engineers has performed multiple laboratory and full-scale evaluations of geosynthetic reinforced pavements. One result from early geosynthetic reinforced pavement evaluations was a pavement design methodology implemented in ETL 1110-1-189: Use of Geogrids in Pavement Construction . Since that time, the evaluations have been primarily focused on comparing performance between varying types of geosynthetic products. While the studies have independently compared the discrete performance of single geosynthetic reinforced sections to unreinforced sections, a comprehensive analysis of available data has not been performed to validate or refine the implemented design methodology. The objective of this effort was to assemble available data from laboratory and full-scale testing conducted at ERDC for the primary purpose of assessing the flexible pavement design methodology presented in ETL 1110-1-189. Simplifying assumptions were made to allow comparison of varying loading and pavement structure conditions. This assessment found that the combined dataset supports the original design curve produced with the equivalent thickness methodology described in ETL 1110-1-189. The updated dataset would reduce the equivalent reinforced thickness by approximately 1.0-inches (25.4 mm) at unreinforced thicknesses less than 14 inches (356 mm), providing a slightly more conservative result. The adjusted data converged with the original equivalency chart at an unreinforced thickness of approximately 16 inches (406 mm).